PENGARUH PENGETAHUAN PERPAJAKAN DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK PELAKU UMKM DI KOTA BANDUNG - Mellinia AlfitriAnti; Eko Setyanto (FKIP, Universitas Banten Jaya, 2023)
Indonesia is a developed country that has a wealth of resourcing. One of country's income comes from taxes. So that mandatory compliance becomes very important in fulfilling tax obligations. On the other hand, a fairly good contribution to the growth of MSMEs is expected to be a compliant taxpayer in paying taxes. Formulation of the problem in this study to determine how influenced of knowledge of taxation and tax penalties on taxpayer compliance MSMEs. The method used is descriptive associative quantitative approach, where researchers try to describe the problem and its solution. The result showed that knowledge of taxation affect the taxpayer compliance of MSMEs, tax penalties affect taxpayer compliance of MSME actors, simultaneously knowledge of taxation and tax penalties affect the taxpayer compliance of MSME actors.